Quorum Sensing Inhibition and Structure–Activity Relationships of β-Keto Esters - Stephanie Forschner-Dancause; Emily Poulin; Susan Meschwitz (Molecules, 2016)
Traditional therapeutics to treat bacterial infections have given rise to multi-drug resistant pathogens, which pose a major threat to human and animal health. In several pathogens, quorum sensing (QS)—a cell-cell communication system in bacteria—controls the expression of genes responsible for pathogenesis, thus representing a novel target in the fight against bacterial infections. Based on the structure of the autoinducers responsible for QS activity and other QS inhibitors, we hypothesize that β-keto esters with aryl functionality could possess anti-QS activity. A panel of nineteen β-keto ester analogs was tested for the inhibition of bioluminescence (a QS-controlled phenotype) in the marine pathogen Vibrio harveyi. Initial screening demonstrated the need of a phenyl ring at the C-3 position for antagonistic activity. Further additions to the phenyl ring with 4-substituted halo groups or a 3- or 4-substituted methoxy group resulted in the most active compounds with IC50 values ranging from 23 µM to 53 µM. The compounds additionally inhibit green fluorescent protein production by E. coli JB525. Evidence is presented that aryl β-keto esters may act as antagonists of bacterial quorum sensing by competing with N-acyl homoserine lactones for receptor binding. Expansion of the β-keto ester panel will enable us to obtain more insight into the structure–activity relationships needed to allow for the development of novel anti-virulence agents.